Classical Hodgkin lymphoma following follicular lymphoma: a case report - Bomi Kim (Journal of Yeungnam Medical Science, 2023)
The simultaneous, composite, or sequential occurrence of follicular lymphoma (FL) and classical Hodgkin lymphoma (HL), both of which originate from germinal center B-cell, is rare. Questions have been raised with regard to the type of tests that pathologists should perform when observing the presence of a “large-cell lymphoma” following an FL and what are the most critical pathological points for diagnosis. Here, we present a case of a classical HL following an FL after administering rituximab-bendamustine (R-Benda) chemotherapy. Furthermore, we also summarized the literature and compared this case with other HLs that followed FLs. A 55-year-old woman was diagnosed with a grade 3A FL of the breast and axillary lymph node masses. She completed six R-Benda chemotherapy cycles for stage IV FL. Twenty-three months after the diagnosis, follow-up image studies showed an increase in the size and number of the lesions. Biopsies of the neck lymph node and liver were performed, and the diagnosis was classical HL. Sequential or composite FL and HL may sometimes develop from the same clone because they share the same genetic alterations, such as B-cell lymphoma (Bcl)-2 or Bcl-6 translocation. When a large-cell lymphoma is found after the treatment of FL, classical HL should be considered a pathological differential diagnosis, and histological, immunohistochemical, or molecular investigations must be considered during the diagnostic process.